2020
DOI: 10.3389/fped.2020.592122
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Glycoprotein Genes in the Inflammatory Process of Kawasaki Disease

Abstract: Background: Kawasaki disease (KD) is the most common form of febrile coronary vasculitis disease to occur in children. Early diagnosis and proper therapy can prevent the complication of coronary artery lesions (CAL). The main pathogenesis of KD is an inflammatory process related to the host's genetic characteristics. In innate human immunity, the interaction of leukocytes and glycoprotein plays an important role against microbes. The purpose of our study was to understand the role of leukocytes' glycoprotein g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…CLEC4D (Dectin-2 cluster ″ of C-type lectin receptor) is expressed exclusively by macrophages and is involved in the occurrence of pancreatic ductal adenocarcinoma [32]. A study by Kuo et al demonstrated the hyperexpression of CLEC4D in peripheral leukocytes during acute phase of Kawasaki disease and its strong correlation to IVIG treatment resistance [33].…”
Section: Discussionmentioning
confidence: 99%
“…CLEC4D (Dectin-2 cluster ″ of C-type lectin receptor) is expressed exclusively by macrophages and is involved in the occurrence of pancreatic ductal adenocarcinoma [32]. A study by Kuo et al demonstrated the hyperexpression of CLEC4D in peripheral leukocytes during acute phase of Kawasaki disease and its strong correlation to IVIG treatment resistance [33].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous research using Human Transcriptome Array 2.0 (HTA 2.0, Affymetrix, Santa Clara), we found that patients with KD exhibited the most increased inflammatory gene expression in the acute phase of KD compared to controls; meanwhile, these genes decrease after patients receive intravenous immunoglobulin (IVIG) therapy [ 9 , 10 , 11 , 12 ]. Among them, KD patients showed significantly increased expression of almost all known toll-like receptors (TLRs), with the exception of TLR3 and TLR7 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have focused on the genes activated in the acute phase of KD [ 10 , 11 ]. In this study, we focused on the suppressed genes in the acute stage of KD and identified novel targets with a clinical significance and potential prognostic value for KD patients.…”
Section: Introductionmentioning
confidence: 99%